Efeito antinociceptivo da N-acetilcisteina e da vitamina E em modelos de nocicepção em roedores - Rossato, Mateus Fortes (2014)
Recently, oxidative stress was indicated as modulator of nociceptive transmission at spinal cord, and that nitric oxide (NO) may activate the TRPV1 in vitro. As no protein thiol compounds (SH) are the main endogenous antioxidants, we decided to investigate the relation between endogenous and exogenous SH, as well as the NO-mediated TRPV1 activation at spinal cord in mice. We observed that the systemic (i.p.), intrathecal (i.t.), but not local (I.pl.) N-acetylcysteine (NAC) administration reduced the nociception, the decrease in spinal SH, raise of thiobarbituric reactive species (TBARS) and 3-nitrotyrosine (3-NT) levels induced by intraplantar capsaicin (CAP). Similarly, i.t. or i.p. NAC administration reduced the nociception (mechanical allodynia) and decrease in spinal SH induced by complete Freund adjuvant (CFA)-induced chronic inflammation. Reinforcing these results, we observed that buthionine-sulfoxamine (BSO), an inhibitor of glutathione synthesis, the main endogenous SH compound, induced a decrease in spinal SH levels, chemical and mechanical allodynia, thermal and mechanical hyperalgesia. To investigate the participation of NO in these processes, we induced spinal nociception (thermal hyperalgesia) by i.t. L-arginine (ARG substrate for endogenous NO synthesis) administration and intraplantar CAP administration. In both cases, the i.t. pre-treatment with NAC or L-NAME (NO synthesis inhibitor) prevented this nociception, as well as the decrease in spinal SH and the raise in nitrite/nitrate (NOx) levels, a stable metabolites of NO. These changes were also prevented by the pharmacological blockade of TRPV1 with the antagonist SB366791, the spinal defunctionalization (induced by i.t. high dose of CAP) and genetic knockdown (induced by repeated oligonucleotide antisense i.t. administration). Thus, we may conclude that SH compounds participate in the spinal nociceptive transmission by neutralizing NO, preventing spinal TRPV1 activation. Therefore, antioxidants as NAC may present antinociceptive effect by this process.